(untitled) (Global Journal of Science Frontier Research, 2019)
After many years and decades, the missing piece is brought to humanity by this time[from prince jessii] in preparation for the beginning of a new era starting from 2020 which is the start of another decade. It is released to enable the world to take the correct shape of living in opposition to the other style which is not according to the blueprints, and to begin a new era of physics involving the impossible. The missing piece is "The space theory", which will reveal man’s universe with regards to its environment.